Analysis of Correction for the Indonesian People's Accelerograph (ARI) based on MEMS ADXL 355 - Satrio, Adji; Hidayat, Nurul; Martha, Agustya Adi; Widodo, Handi Sulistyo; Nugroho, Hapsoro Agung; Akram, Rafi Syah; Sutejo, Bayu; Prakoso, Tio Azhar (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Indonesia, geographically situated on the Pacific Ring of Fire, has one of the highest potentials for earthquake and tsunami disasters worldwide, second only to Japan. These seismic events pose significant threats, including loss of life and infrastructure damage. One of the key strategies to mitigate earthquake risks is the implementation of Earthquake Early Warning System (EEWS) technology, which heavily relies on the spatial distribution of accelerographs. The Indonesian People's Accelerograph (ARI) has been designed as an affordable and independently built solution to record ground vibration acceleration, utilizing the MEMS-based ADXL 355 sensor and an ESP32 microcontroller for efficient EEWS implementation. This study focuses on the development and correction of the ARI system to enhance instrument response accuracy by analyzing ground acceleration vibration data through an inversion-based method applied to ARI recordings. The results demonstrated that the ARI accelerograph exhibits pole values of 1.31260317e-07 and -2.43562359e-02, zero values of -1.23898531e-06 and 2.77232055, and a gain of 72.97. These findings confirm that the ARI accelerograph provides reliable seismic data, highlighting its potential as an essential tool in reducing earthquake risk and mitigating seismic disaster impacts through improved earthquake early warning capabilities.